QISHKI ILDIZMEVALI O’SIMLIKLAR AGROTSENOZINING DALASIDA ZARARKUNANDA VA BEGONA O‘TLARI - Fayzullayev Farrux, Fayzullayev Farrux; Botirov Xidirali X.F, Botirov Xidirali X.F (Actual problems and prospects of the study of the fauna, 2024)
The article describes the flora and fauna of weeds in the field of winter root vegetables in the gray soils of Samarkand region. In winter, when the stock of weeds is 1-3 pieces per 1m2, the attack of autumn moth, cotton weevil, thrips and leaf-eating pests increases. Against them, Nabu (1.5 kg/ha), Nitran (3.3-6.0 l/ha) and Promethrin (2.0-3.0 l/ha) drugs are recommended; translator;